Summer Watering Patterns of Mule Deer in the Great Basin Desert, USA: Implications of Differential Use by Individuals and the Sexes for Management of Water Resources - Andrew V. Shields; Randy T. Larsen; Jericho C. Whiting (The Scientific World Journal)
Changes in the abundance and distribution of free water can negatively influence wildlife in arid regions. Free water is considered a limiting factor for mule deer (Odocoileus hemionus) in the Great Basin Desert. Consequently, a better understanding of differential use of water by individuals and the sexes could influence the conservation and management of mule deer and water resources in their habitats. We deployed remote cameras at all known water sources (13 wildlife water developments and 4 springs) on one mountain range in western Utah, USA, during summer from 2007 to 2011 to document frequency and timing of water use, number of water sources used by males and females, and to estimate population size from individually identified mule deer. Male and female mule deer used different water sources but visited that resource at similar frequencies. Individual mule deer used few water sources and exhibited high fidelity to that resource. Wildlife water developments were frequently used by both sexes. Our results highlight the differing use of water sources by sexes and individual mule deer. This information will help guide managers when siting and reprovisioning wildlife water developments meant to benefit mule deer and will contribute to the conservation and management of this species.